Micro-tensile testing of reduced-activation ferritic steel F82H irradiated with Fe and He ions. (December 2018) - Miura, Terumitsu; Fujii, Katsuhiko; Fukuya, Koji; Ando, Masami; Tanigawa, Hiroyasu
Highlights: Micro-tensile testing was conducted for F82H steel irradiated with Fe and He ions. Unirradiated yield and tensile strength was close to the data for large specimen. Increase in yield and tensile strength by Fe ions irradiation was clearly observed. Additional increase in the strength was detected for dual Fe and He ions irradiation. Abstract: Micro-tensile tests were conducted on reduced-activation ferritic steel F82H specimens after irradiation with Fe and He ions. The displacement damage levels were 50 and 200 dpa, and helium concentrations were 0, 2000 and 5000 appm. The specimens had dimensions of 8 × 1 × 1 µm for the gage section and they were tension tested at room temperature in a vacuum. The yield strengths of the unirradiated specimens were close to the literature value reported for a large, unirradiated specimen. The increases in yield strength and ultimate tensile strength due to Fe ion irradiation were clearly observed. The loss of work hardening was confirmed for the 200 dpa specimens (0 or 2000 appmHe). Higher yield strength and ultimate tensile strength were confirmed for the 50 dpa/5000 appmHe specimen compared to the no helium specimen (50 dpa/0 appmHe). However, no apparent helium effects were confirmed for the 200 dpa/2000 appmHe specimen by the micro-tensile test at room temperature.